(untitled) (Journal of Informatics Education and Research, 2023)
This research examines how leadership development programmes may affect workplace communication and climate. Strategic leadership development investments are expected to grow as organisations realise the importance of leadership in navigating the current corporate landscape. The research will examine the complex relationships between leadership development, communication, and the workplace. Studying the context and relevance of leadership development, including Situational Leadership and Transformational Leadership theories, is expected. Success will depend on leaders’ adaptation to their teams’ needs and preparedness and imaginative communication. The research will also focus on active listening, dispute resolution, feedback, and ongoing development to enhance workplace communication. Leadership development is intended to be a strategic investment that promotes professional advancement, employee happiness, and work-life balance. Leadership development programmes face organisational opposition and budget restrictions, but the research will recognise their merits. A comprehensive literature study will examine current academic papers to identify leadership development program-influenced transformational patterns. Researchgate, MDPI, ScienceDirect, and Google Scholar were searched for "leadership development" and "workplace communication." During data extraction, authorship, publication year, research methods, and findings were documented. This study concludes that leadership development may shape organisational communication and the work environment, helping organisations navigate the changing business landscape.